TRADITIONAL AND MODERN SCIENCES TECHNOLOGIES IN INDIA - Pathak, Mangesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Indian subcontinent encompasses a diverse array of knowledge systems and practices, which coexist in a fascinating range today. In this presentation, the following key points will be covered. The Traditional Indian Knowledge Systems are defined by a distinct nature and set of characteristics, which can be summarised as folloSpecific illustrations from various sectors of Science and Technology. These traditional knowledge systems exhibit distinct characteristics that set them apart from their counterparts. Consider the potential for connections and collaboration between these different traditions both in the present and in potential future scenSpell out some specific ways in which these traditional knowledge systems differ from their modern counterparts. Reflect on the possibilities of inter-linkages and cooperation between these varying traditions as they occur today as well as in terms of future possibilities. Contemporary scholarships in science, focusing on disciplines such as Sociology, Epistemology, or Historiography, generally rely on the premise that modern Western science serves as the paradigm for a "Scientific Knowledge System". Accepting this criterion would likely render it improbable to find scientific knowledge in any other tradition since we have not identified knowledge systems that are identical to the modern Western knowledge system elsewhere. To overcome this constraint, we must first develop an unbiased standard for designating a knowledge system as "scientific". We will first focus on a particular branch of the traditional Indian Knowledge System and evaluate it according to criteria that are generally accepted, in order to determine how it stacks up as a scientific pursuit. We’ll focus on the specific characteristics of traditional knowledge systems that distinguish them from modern systems of knowledge. Key points that will be emphasised are: Approach to measurement and quantification, outlook towards experimental methods, parameters used to build theories as well as the social organisation of knowledge. The social organisation of knowledge is a fascinating aspect. Knowledge in India prevails and is expressed at varied levels in diverse areas. In many areas such as medicine, arithmetic, agriculture, grammar, language, dance, music and astrology, to name just a few there is wide and extensive knowledge both at the level of classical texts and folk traditions. They are commonly referred to as: “Shastra” and “Lok Parampara” respectively. There is every reason to believe that on the ground today folk traditions are widespread in various walks of life and vibrant. Research on traditional knowledge by scientists from the mainstream science and technology institutions is not a new phenomenon. However a lot of this research suffers from the limitations of a mind set which essentially looks upon physical resources as well as technologies and knowledge of traditional societies as “raw material” that needs to be prospected so that one may extract what is worth while and useful to incorporate it into a modern western framework. This is a hang over of a colonial past and today there is an increasing perception that such activities do not lead to revitalisation of traditional knowledge or wholesome development of the communities involved. However in recent times there have been instances of healthy collaboration between various knowledge systems and we shall spell out some examples and possibilities of how different system scan workhand in hand to meet specific requirement or social goals.